Primary health care as a pillar of the End-TB strategy: a scoping review - Mahmud, Aidalina; Abdul Rahim, Arifah; Ahmad Zaidi, Nur Adnin (International Journal of Public Health and Clinical Sciences, 2020)
Background: Primary health care (PHC) may have elements which can contribute to the management of tuberculosis (TB), particularly the ‘End TB’ effort based on the Sustainable Development Goals target 3.3. The aim of this review was to summarise available evidence in countries of high TB burden to determine if the PHCs in these selected countries fulfil their elements. Materials and Methods: The Arksey and O'Malley six-stage methodological framework for scoping review was used. MEDLINE/PubMed and Google Scholar were used. Additionally, hand search of the reference lists of journal articles was conducted. Search terms used were “tuberculosis, TB diseases, TB treatment, and primary health care”. Inclusion criteria were articles in the English language, of any study methodology and published online between the years 2008 and 2018. Extracted data were tabulated into two standardised templates: the PCC (Population / Concept / Context) framework and template to determine if the PHCs involved in providing TB treatment fulfilled the pre-determined criteria. Result: Ten of the 16 studies analysed showed that the PHC fulfilled the criteria for primary health care and provided successful TB treatment. Five of 16 studies showed that PHCs which used the community-based approach did better in providing TB management compared to those which relied mainly on the services provided at the static clinic. Conclusion: Primary Health Care is a promising and important pillar of the End TB Strategy. The core elements and role of PHC as the first contact with the population is the main force in achieving the SDGs generally and ending TB specifically.